Keragaan dan Karakter Fase Pertumbuhan In Vitro Putatif Mutan Anggrek Hitam Kalbar Hasil Induksi Mutasi Secara Kimia: Performance and Characteristics of the In Vitro Growth Phase Putative Mutant Black Orchid in West Kalimantan Results of Chemical Induction of Mutations - Asnawati, Asnawati; Listiawati, Agustina (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2024)
Putative mutants of West Kalimantan black orchids obtained through mutation activities need to be evaluated for their growth character and performance early, starting from the vegetative phase at the in vitro stage. This study aims to determine the performance and character of the in vitro putative growth phase of West Kalimantan black orchid mutants. The research was carried out at the Biotechnology Laboratory of the Faculty of Agriculture, Tanjungpura University from April-October 2023. The experiment was conducted using Complete Randomized Design. As a treatment were 6 in vitro bud clones of black anggtek (5 putative mutant clones derived from 5 EMS concentration levels and 1 wild type plant clone as control). The clones are K (as control plant) and M, N, O, P and Q clones each resulting from EMS concentration 0; 0,25; 0,50; 0,75; 1.00 and 1.25%. The treatment was repeated 5 times and each repetition consisted of 5 samples, resulting in a total of 150 experimental units. Variables observed include: Changes in plant weight, time of emergence of shoots, time of emergence of roots, increase in the number of leaves, number of shoots and number of roots. The results showed that the increase in the number of leaves and weight of putative mutant plants endemic to West Kalimantan black orchids from clone M was better than control plants (K) and other clones (clones N, O, P and Q), For the character of the number of shoots and roots, all mutant putative clones produced a lower number of shoots and roots than control plants (K). The results of plant characterization, found differences in growth characters in all putative clones of black orchid mutants except the O clone, when compared to control plants. Keywords : Black orchid, In vitro, Performance, Putatif Mutant, Vegetative growth